THEORETICAL PRINCIPLES OF DEFINITION AND CLASSIFICATION OF PUBLIC SERVICES - Gunbina , E. (Theory and Practice of Public Administration, 2020)
In the late 1970s and early 1980s, public administration was reformed in many parts of the world. The main concept of this reform was to review the role and content of the public administration system. The bureaucratic model of this system, which formed the basis of its activities, became inefficient. closed and hampered further social development. As a result, most democracies around the world (especially the United States and the United Kingdom) have begun to pay attention to the principles and methods of organizing and operating business management systems. Management in these structures functioned in conditions of fierce market competition, where we had to constantly “compete” for the consumer of products, by providing him with services (goods) in a better and more efficient way. All this led to an attempt to implement the methods and methods of management developed in business structures to the public sector. It is at this time that the concept of the “service state” emerges, the main content of which reorients public administration from the implementation of regulations and norms to the provision of services. Ukraine has started administrative reform since 1998, one of the components of which is the introduction of a service-oriented approach to public administration. Therefore, the article examines the theoretical foundations of the definition and classification of public services is relevant. The article argues that the transition to a service-oriented state reproduces the need to reorient the activities of public administration from the administrative process to the provision of services. The service itself involves a certain type of activity to provide certain benefits. The public service is defined by the fact that these benefits are provided directly by public authorities (state or municipal) or indirectly through various enterprises by financing these services from the budget and aimed at activities that solve important problems of society. The article considers the classification of public services depending on the type of services, the subject of services, activities.